The Concept of Friend in Publicistics - Vaičiulytė-Semėnienė, Loreta (Vilnius University Open Series, 2020)
This article deals with the contents of friend based on the different forms of the noun friend (Lith. draugas). A balance is drawn between the structural and cognitive approach to its meaning. The study is grounded on 700 publicistics sentences collected in the Corpus of the Modern Lithuanian Language compiled by the Centre for Computational Linguistics at Vytautas Magnus University in Kaunas.The study has showed that friend is perceived as a person who acts out of love at a certain place and time.In terms of love, there are friends that are tied (rather) by bonds of fellow-feeling (The Dictionary of the Standard Lithuanian Language – DSLLe friend definition 1, 2) (In the beginning, they were huge friends and liked each other a lot; Friends love you) and those who (rather) share bodily intimacy (DSLLe friend definition 3). On the basis of the criterion of love, the relationship between a person and their friend can revolve in circles: a friend by DSLLe definition 1 or 2 becomes a friend by DSLLe definition 3 (After all, our friends, then families would begin and end in theatre), and vice-versa; a friend by DSLLe definition 2 can become a friend by DSLLe definition 1, and so on. In other words, friendship as fellow-feeling can transform into bodily love, and once bodily love goes away, friends, as husband and wife, can become/remain friends again as very close acquaintances.Someone who loves themselves unconditionally knows how to love another person that way. This kind of friend favours themselves and the other person. Mutual favour unfolds over time spent together, when mutual affinity is found/discovered. That time creates good, real friends that become a value (I treasure good friends the most. We have a bunch of very good mates that we have jolly good time with. We talk, we dance. Or we simply spend time in very comfortable silence).To be a friend, is to become a friend (DSLLe friend definition 1–3 vs. DSLLe friend definition 4). To oneself, first and foremost. The type of friend a person is to themselves is usually revealed through the person’s (myself) relationship with another person they know to a greater or lesser extent. That other person can either be a familiar (DSLLe friend definition 3) or strange (DSLLe friend definition 1, 2) person and/or non-person. Friendship between a person and a thing is a one-way street: it is untrue. What matters in this type of friendship, is not the time spent together, but rather benefit and/or pleasure. In other words, the person (myself) cannot be defined through the understanding of friend, i.e. on the basis of the criterion of similarity: tell me who your friend is, and I will tell you who you are.In terms of time, friends can be defined to a lesser or greater extent (DSLLe friend definition 1, 3 (These friends of father’s go back to Smetona’s era; the friend of my life) resp. DSLLe friend definition 2 (Could it be that she only remained a mere dodgeball friend?)). This is also more or less the case in point when it comes to the aspect of location: well-defined (DSLLe friend definition 3), better-defined (DSLLe friend definition 2; cf.: my roommate) or undefined (DSLLe friend definition 1) friends.The friendship between man and God can be one-way (from God to man) an (become) two-way (between God and man). They both are driven by love, hence are real.
Keywords: noun friend; concept; structural semantics